Prosedur Penerjemahan Kuplet pada Terjemahan Nama-Nama Kuliner Indonesia - Mahmud, Erlina Zulkifli (Kementerian Sekretariat Negara Republik Indonesia, 2021)
This research article focuses on the use of couplets translation procedures and the object of the research is the names of food and drinks in Indonesian culinary written in a novel and its translation. The objectives of this research are to describe what translation procedures involved in the couplets and what semantic components used in the equivalences. The research uses descriptive-comparative method. The results show that the transference always involves in the couplets and the semantic components mostly reveal the ingredients of the food or the drinks and followed by the taste and or by the appearance. Keywords: couplets, Indonesian culinary, semantic component, translation procedure.